Pembelajaran Berbasis Teknologi Informasi: Ikhtiar Guru dalam Meningkatkan Minat Belajar Peserta Didik - Alfiani, Laily Nur (Institut Agama Islam Negeri Lhokseumawe, 2019)
This study discusses the implementation of information technology-based learning media to increase interest in learning on the subjects of PAI. Media serves as a tool that also plays an important role. In today's technological advancement enables students to learn from anywhere and anytime and anywhere by utilizing technology results. Therefore, teacher roles and tasks shift from role as learning resource to role as manager of learning resource. Through the use of various sources it is expected that the quality of learning will increase. Information Technology as a medium of learning is a media set of tools and technology resources used to communicate, create, disseminate, store and process information or technology that can reduce space and time constraints to retrieve, move, analyze, present, store and transmit data information into a information. Where The development of information and communication technology has an influence on the world of education, especially in the learning process. By using information technology-based media is expected to increase or develop student interest in the subject of PAI